Application of real-time PCR for analysis canine meat (Canis lupus familiaris) in goat's satay for halal authentication study - Lily Arsanti Lestari; Wan Nurul Aini; Marlyn Dian Laksitorini; Yuny Erwanto; Agustina Ari Murti Budi Hastuti; Mohammad Zainal Abidin; Nurulia Hidayah; Muhammad Jefriyanto Budikafa; Abdul Rohman (Open Veterinary Journal)
Background: Canine meat (CM) is one of the non-halal meats prohibited for consumption by the Muslim community. Due to low price compared with beef, CM is typically used as meat adulterants in halal-food based products such as Satay and meatballs to get the economic profits.